The Victorian intergenerational migrant cohort: Socioeconomic outcomes 1851-1901 - Thomas, R (2018)
Intergenerational outcome (IO) studies model the transmission of socioeconomic status between familial generations. Given the balancing of time horizons and future expectations implicit in migration decisions, IO studies are particularly salient to an empirical understanding of migration. However, few datasets exist which provide the necessary longitudinal observations for migrant populations, therefore such IO studies remain rare. This paper presents a novel cohort of 288,000 individuals from fifty years of English census data (1851-1861 and 1881-1901), representing some 36,000 core family groups who originated beyond the national boundary of England prior to 1851. The intercensal linking method employed here (network persistence linkage, or NPL) is also unique. It exploits persistent coresident proximity to enrich individual identifiers and includes an equal number of females as well as males. Socioeconomic outcomes are defined with the HISCAM scale, a measure of social proximity derived by statistical correspondence analysis of occupations within historic civil and genealogical records. Descriptive analysis of outcomes over three generations shows that immigrants had significant socioeconomic mobility, especially females, although this was not always an upward move. Immigrant families with very advantaged positions may have experienced rapid regression to the mean. An ordinary least squares (OLS) estimate of intergenerational transmission finds that both males and females transmitted a significant effect to their children’s status through their own socioeconomic prestige. This effect is stronger between the immigrant and his/her child than between that child and the third generation. The country of origin had a significant effect on the status of both subsequent generations, although there is also evidence that this dissipated among the grandchildren of British Isles immigrants. This study demonstrates that it is possible to link females as well as males across historical population datasets, and that omitting them from intergenerational outcome models may overestimate inheritance and underestimate mobility.